Effect of Investment Decisions, Funding Decisions and Dividend Policies on Company Value in The Jakarta Islamic Index - Mesis Rawati; Iiz Izmuddin; Anggi Setya Prayoga; Loso Judijanto; Al-Amin; Hadi Subeno (Proceeding of The International Conference on Business and Economics, 2024)
This research aims to test whether investment decisions, funding decisions and dividend policy influence company value. The data used in the research is secondary data. The population of this research is companies registered in the Jakarta Islamic Index (JII) 70 for 2018-2021. Determining the sample in the research used the porpusive sampling method with special criteria to obtain 68 data. The results of this research prove that the influence of investment decisions on company value is 0.256 > 0.05 and the calculated t value is 1.147 < 1.99714. There is no influence of investment decisions on value. Company. The influence of funding decisions on company value is 0.000 < 0.05 and t count is 6.384 > 1.99714. There is a significant influence of funding decisions on company value. The influence of dividend policy on company value is 0.116 > 0.05 and the calculated t is 1.595 < 1.99714 so it can be concluded that there is no influence of dividend policy on company value.